2013
DOI: 10.1371/journal.pone.0076618
|View full text |Cite
|
Sign up to set email alerts
|

A Community Study of the Psychological Effects of the Omagh Car Bomb on Adults

Abstract: BackgroundThe main aims of the study were to assess psychological morbidity among adults nine months after a car bomb explosion in the town of Omagh, Northern Ireland and to identify predictors of chronic posttraumatic stress disorder symptoms.MethodA questionnaire was sent to all adults in households in The Omagh District Council area. The questionnaire comprised established predictors of PTSD (such as pre-trauma personal characteristics, type of exposure, initial emotional response and long-term adverse phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
3
12
1
1
Order By: Relevance
“…Diehle, de Roos, Meiser-Stedman, Boer, & Lindauer, 2015;Mitchell, Brennan, Curran, Hanna, & Dyer, 2017) as well as adults (e.g. Duffy, Bolton, Gillespie, Ehlers, & Clark, 2013). Maladaptive appraisals have been shown to prospectively predict PTSD symptom severity and the maintenance of PTSD symptoms in adults (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Diehle, de Roos, Meiser-Stedman, Boer, & Lindauer, 2015;Mitchell, Brennan, Curran, Hanna, & Dyer, 2017) as well as adults (e.g. Duffy, Bolton, Gillespie, Ehlers, & Clark, 2013). Maladaptive appraisals have been shown to prospectively predict PTSD symptom severity and the maintenance of PTSD symptoms in adults (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates (8%) were reported among the general population in the US 10,11 . In contrast, much higher rates (43%) were reported among survivors of suicidal explosions in Iraq, 12,13 and among risk groups in other countries 14,15 . Similarly, higher rates were reported among undergraduate and secondary school students in Baghdad but using different measurement instruments 16 .…”
Section: Introductionmentioning
confidence: 87%
“…A possible explanation for the low PTSD prevalence might be related to the high population resilience which was also implicated in similar studies in Lebanon 8,34 . A recent study using a different tool (Harvard questionnaire) among high risk samples had reported a much higher PTSD rate (43%) among survivors exposed to suicidal explosions in Kerbala city, 12 and in other cities in in Iraq, 13 and in many other studies in Gaza strip and North Ireland 14,15 . The gender difference in PTSD prevalence with female predominance was similar to most reviewed studies in the developed countries 42 .…”
mentioning
confidence: 96%
“…본 연구의 변인들 간 상관은 (Norris et al, 2002;Chang et al, 2005;Tang, 2006;Weems et al, 2007;Duffy et al, 2013) (Otto et al, 2006;Lommen et al, 2009;Lee JL et al, 2011)…”
Section: 변인들 간 상관관계unclassified